Magmatic and Metasomatic Effects of Magma–Carbonate Interaction Recorded in Calc-silicate Xenoliths from Merapi Volcano (Indonesia). (20th April 2020) - Whitley, Sean; Halama, Ralf; Gertisser, Ralf; Preece, Katie; Deegan, Frances M; Troll, Valentin R
Abstract: Magma–carbonate interaction is an increasingly recognized process occurring at active volcanoes worldwide, with implications for the magmatic evolution of the host volcanic systems, their eruptive behaviour, volcanic CO2 budgets, and economic mineralization. Abundant calc-silicate skarn xenoliths are found at Merapi volcano, Indonesia. We identify two distinct xenolith types: magmatic skarn xenoliths, which contain evidence of formation within the magma; and exoskarn xenoliths, which more likely represent fragments of crystalline metamorphosed wall rocks. The magmatic skarn xenoliths comprise distinct compositional and mineralogical zones with abundant Ca-enriched glass (up to 10 wt % relative to lava groundmass), mineralogically dominated by clinopyroxene (En15-43 Fs14-36 Wo41-51 ) + plagioclase (An37-100 ) ± magnetite in the outer zones towards the lava contact, and by wollastonite ± clinopyroxene (En17-38 Fs8-34 Wo49-59 ) ± plagioclase (An46-100 ) ± garnet (Grs0-65 Adr24-75 Sch0-76 ) ± quartz in the xenolith cores. These zones are controlled by Ca transfer from the limestone protolith to the magma and by the transfer of magma-derived elements in the opposite direction. In contrast, the exoskarn xenoliths are unzoned and essentially glass-free, representing equilibration at sub-solidus conditions. The major mineral assemblage in the exoskarn xenoliths is wollastonite + garnet (Grs73-97 Adr3-24 ) + Ca-Al-rich clinopyroxene (CaTs0-38 ) + anorthite ± quartz, with variable amounts of either quartz or melilite (Geh42-91 ) + spinel. Thermobarometric calculations, fluid-inclusion microthermometry and newly calibrated oxybarometry based on Fe 3+ /ΣFe in clinopyroxene indicate magmatic skarn xenolith formation conditions of ∼850 ± 45°C, < 100 MPa and at an oxygen fugacity between the NNO (nickel–nickel oxide) and HM (hematite-magnetite) buffer. The exoskarn xenoliths, in turn, formed at 510–910°C under oxygen-fugacity conditions between NNO and air. These high oxygen fugacities are likely imposed by the large volumes of CO2 liberated from the carbonate. Halogen- and sulphur-rich mineral phases in the xenoliths testify to infiltration by a magmatic brine. In some xenoliths, this is associated with the precipitation of copper-bearing mineral phases by sulphur dissociation into sulphide and sulphate, indicating potential mineralization in the skarn system below Merapi. The compositions of many xenolith clinopyroxene and plagioclase crystals overlap with that of magmatic minerals, suggesting that the crystal cargo in Merapi magmas may contain a larger proportion of skarn-derived xenocrysts than previously recognized. Assessment of xenolith formation timescales demonstrates that magma–carbonate interaction and associated CO2 release could affect eruption intensity, as recently suggested for Merapi and similar carbonate-hosted volcanoes elsewhere.